Estimación por muestreo del índice de Gini para las localidades de Bogotá usando funciones en R (2015)
In this time it is important the data with respect to inequality measures in economics and social science. In this paper we use this information to calculate the Gini index. This index uses the information about the income in a population, speciﬁcally in Bogot´a D.C. for their 19 localities. We use the multipurpose survey for Bogotá D.C. in 2011 and use the modules for this analysis in each locality deﬁning the variables that included information about incomes per household.